PENGARUH Pengaruh Motivasi Bisnis dan Kesadaran Halal Terhadap Keputusan Sertifikasi Halal Gratis Self Declare Bagi UMKM di Ponorogo - MUH. NAJIB AMRIL HUDA; MOH. FAIZIN (Niqosiya: Journal of Economics and Business Research, 2024)
The Halal Product Guarantee Organizing Agency in 2023 will open a program of 1 million free halal certifications for UMKM in the Self Declare category. This will encourage business motivation and halal awareness from business actors to make the decision to register for free halal certification. However, in reality, awareness of the halalness of a product and motivation of business actors is still relatively low. The aim of this research is to test and analyze partially or simultaneously the variables of business motivation and halal awareness regarding the decision to implement free halal certification in the Self Declare category for UMKM in Ponorogo district. This type of research is quantitative research using primary data. The sampling technique uses probability sampling techniques, with data collection techniques using questionnaires and the number of respondents is 100 respondents. The research results show that business motivation has a significant influence on the decision to implement free halal certification in Ponorogo Regency, halal awareness has a significant influence on the decision to implement free halal certification in Ponorogo Regency. and simultaneously business motivation and halal awareness have a significant influence on the decision to implement free halal certification in Ponorogo Regency, namely 59.1%.